1998
DOI: 10.1016/s0014-5793(98)01451-3
|View full text |Cite
|
Sign up to set email alerts
|

Homomultimeric protease in the hyperthermophilic bacterium Thermotoga maritima has structural and amino acid sequence homology to bacteriocins in mesophilic bacteria

Abstract: A novel homomultimeric protease ( s 669 kDa), based on 31 kDa subunits, was purified from cell extracts of the hyperthermophilic bacterium Thermotoga maritima. This protease exhibits activity toward chymotrypsin and trypsin substrates, optimally at 90³C and pH 7.1, and has a half-life of 36 min at 95³C. Transmission electron microscopy established that the protease consists of a large globular assembly which appears circular from the front view. The function of this protease in T. maritima remains unclear, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…One such class is the encapsulins whose shell proteins possess a fold previously found only in viral capsids. However, other encapsulin nanocompartments have been suggested to perform different functions, including antibacterial activity in Brevibacterium linens (Valdes-Stauber & Scherer, 1994), proteolytic activity in T. maritima (Hicks et al, 1998), and lignin degradation activity in Rhodococcus jostii RHA1 (Rahmanpour & Bugg, 2013). To date, only a few have been identified on the basis of structural similarity but we anticipate that this set will grow considerably.…”
Section: A Diversity Of Encapsulin Functions Natural and Syntheticmentioning
confidence: 99%
See 1 more Smart Citation
“…One such class is the encapsulins whose shell proteins possess a fold previously found only in viral capsids. However, other encapsulin nanocompartments have been suggested to perform different functions, including antibacterial activity in Brevibacterium linens (Valdes-Stauber & Scherer, 1994), proteolytic activity in T. maritima (Hicks et al, 1998), and lignin degradation activity in Rhodococcus jostii RHA1 (Rahmanpour & Bugg, 2013). To date, only a few have been identified on the basis of structural similarity but we anticipate that this set will grow considerably.…”
Section: A Diversity Of Encapsulin Functions Natural and Syntheticmentioning
confidence: 99%
“…One subset of encapsulin operons also code for a dyedecolorizing peroxidase (DyP) or for a ferritin-like protein (Flp), which was taken to suggest a role in the oxidative-stress response (Sutter et al, 2008), now amply confirmed in the M. xanthus system. However, other encapsulin nanocompartments have been suggested to perform different functions, including antibacterial activity in Brevibacterium linens (Valdes-Stauber & Scherer, 1994), proteolytic activity in T. maritima (Hicks et al, 1998), and lignin degradation activity in Rhodococcus jostii RHA1 (Rahmanpour & Bugg, 2013).…”
Section: A Diversity Of Encapsulin Functions Natural and Syntheticmentioning
confidence: 99%
“…For example, Connaris et al (1991) and Blumentals et al (1990) reported that gelatin-based zymograms of cell-free extracts from P. furiosus revealed the presence of up to 13 clearing zones, some of which were later attributed to multiple versions of a single protease (Halio et al 1996. Similar experiments with T. maritima revealed an even more limited set of proteases than observed in P. furiosus (Hicks et al 1998). Genome sequence data, however, indicate that the proteolytic genotypes of these organisms are more expansive than can be inferred from zymogram analyses.…”
Section: Inferring Protease Inventory From Genomic Sequencesmentioning
confidence: 92%
“…(Halio et al 1996, Voorhorst et al 1996, Thermococcus stetteri (Klingeberg et al 1995), A. pernix (Sako et al 1997) and P. abyssi (Dib et al 1998) (see Table 3). The only protease isolated from T. maritima thus far is a homomultimeric protease that has moderate amino acid sequence identity to bacteriocins from mesophilic bacteria (Hicks et al 1998). Within the classical classification scheme for proteases, namely, serine, aspartic, metallo and cysteine, the majority of the enzymes characterized to date from hyperthermophiles has been extracellular, and belongs to the serine class.…”
Section: Atp-independent Proteases In Hyperthermophilesmentioning
confidence: 99%
See 1 more Smart Citation